PEMBUATAN MESIN PERAJANG KETELA SERBA GUNA UNTUK INDUSTRI PATILO DAN CERIPING KETELA SKALA KECIL - Karyono, Slamet; Wagiran, Wagiran (Universitas Negeri Yogyakarta, 2005)
A group called SARILA in Kauman, Dadapayu, Semanu, Gunung kidul, had a problem of low production quality and capacity in their busi ness of making patilo and fried cassava chips because the work of cutting and scraping the basic material for their products, cassava, was done manu ally by using simple tools that caused the cassava to break when cut so that the resulting chips were also in broken conditions and the manual work caused the workers to quickly become exhausted. Therefore, the main objec tive of one voucher program was to enable the workers to do their work me chanically instead of manually.It had to be able to design and produce an easily-operated cassava processing machine with a frame strong enough to withstand vibrations and do two kinds of work, cutting and scraping cassava, easily, accurately, and simultaneously. An ergonomic table also had to be developed to ensure long-lasting use of the machine in the cassava processing. The machine at last successfully produced is 90 em in length, 60 em in width, and 90 em in height, designed high enough to enable the operator to do the work easily in a standing-up position. Stainless steel plate material is applied on all parts having direct contact with the cassava processing. The frame of the machine is made of 5-cm rectangular steel profiles to ensure its being strong enough to withstand operation. An electrical motor with a power of Y2 HP and pul ley-and-belt transmission aids the operation. Such transmission enables the cutting and scraping parts to operate simultaneously at different speeds. The position of the cutting tool can be adjusted for desired thickness. Except the frame, all parts of the machine are designed according to a knock-down sys tem for easy replacement of broken parts.The result of a performance test on the machine has shown that itcan be operated easily without the operator becoming quickly exhausted. Compared to what is produced in the old ways, the product looks better; it is smoother, and there is less cassava fibers. The product capacity of the ma chine is about 50 kg every 50 minutes from its cutting process and 50 kg every 75 minutes from its scraping process. During operation, there is no vibration on its frame. It shows that the construction design is strong enough to withstand the vibration of the motor rotation and cassava processing.Keywords: cassava, multipurpose machine, cutting and scraping